On decomposability of matrix polynomials with coefficients of quasi-simple structure - Shavarovsky , B. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The decomposability of matrix polynomials with commuting coefficients of quasi-simple structure into regular factors and the solvability of the corresponding matrix polynomial one-sided equations are investigated.